2004
DOI: 10.1002/masy.200450920
|View full text |Cite
|
Sign up to set email alerts
|

Styrene polymerization by ziegler‐natta catalysts based on bis(salicylaldiminate)nickel(II) complexes and methyl aluminoxane

Abstract: The homopolymerization of styrene by using different catalytic systems based on bis(salicylaldiminate)nickel(II) and methylaluminoxane was investigated. In particular, the effect on catalyst activity and polymer characteristics by electron withdrawing groups located on the phenolic moiety was studied. The influence of the bulkiness of the substituents on the N‐aldimine ligand was also ascertained. Finally the catalytic performances were investigated as a function of the main reaction parameters, such as temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The complexes showed good activity, but a black solid, probably consisting of Pd(0), was formed during the reaction. 5 The authors consider the possibility that the deactivation of the Pd catalysts, reported by Gregorio et al, 146 could be due to the lower temperature (120°C) applied in the reaction. Similar to the Pd precursors, Burk et al 92 noticed the formation of a heterogeneous phase when employing Rh complexes.…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The complexes showed good activity, but a black solid, probably consisting of Pd(0), was formed during the reaction. 5 The authors consider the possibility that the deactivation of the Pd catalysts, reported by Gregorio et al, 146 could be due to the lower temperature (120°C) applied in the reaction. Similar to the Pd precursors, Burk et al 92 noticed the formation of a heterogeneous phase when employing Rh complexes.…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 99%
“…Homogeneous Ni, Ru, Rh and Pd complexes were also studied at higher temperatures (200°C) by Carlini and coworkers. 5,81 Using MeONa, Pd(0) and PdIJII) complexes showed remarkable activity for the production of isobutanol from methanol and n-propanol. The oxidation state of the palladium precursor appeared to be unimportant with respect to its activity.…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 99%
See 3 more Smart Citations